TIMP1 gene was highly expressed in LUAD tissues and regulated malignant cell- Treg interactions. - Yanfeng Xue (465345) (2025)
(A) Representative immunohistochemical (IHC) staining of TIMP1 in normal (n = 8) and LUAD tissues (n = 8) (scale bar: 100 μm), Three fields of view were selected from each histopathological section. (B) Quantitative H-score analysis of TIMP1 staining intensity (normal vs LUAD). *p < 0.05; **p < 0.01; ****p < 0.0001. (C) Multiplex immunofluorescence (mIF) demonstrating spatial co-localization of FoxP3 + Tregs and TIMP1 + cells (scale bar: 100 μm). (D) Enumeration of TIMP1+ and FoxP3 + cells in normal (n = 3) and tumor tissues (n = 3), Three fields of view were selected from each histopathological section. *p < 0.05; **p < 0.01; ****p < 0.0001.